EVALUASI ANALISIS EFEKTIFITAS COPY NASKAH DENGAN MENGGUNAKAN ANALYTIC HIERARCHICAL PROCESS (Jurnal Pilar Nusa Mandiri, 2012)
Progress in the field of business needs the support of the promotion, promotion measures can be done in  various  ways,  one  of  which  is  measured  in  the  areas  of  advertising,  as  outlined  in  a  manuscript copy. There are a number of methods to evaluate the manuscript copy of which Direct Rating Method (DRM), EPIC Model and Customer Response Index (CRI). For an evaluation copy of the script there is a measurement method of comparison can be done with the Analytic Hierarchical Process (AHP). AHP  is  a  method  that  is  widely  used  in  decision  making  and  scientific  part  of  the  decision  support system,  known  as  Dicission  Support  System  (DSS).  In  the  discussion  of  this  paper  is  intended  to evaluate  the  effectiveness  of  each  level,  from  the  three  models  are  used  as  a  measure  to  assess  the effectiveness of course seen the manuscript copy of each of the variables used. AHP didigunakan as advanced  testing  seen  from  some  of  the  other  variables  if  the  data,  formulation,  design  output,  and transfer  knowledge.  At  the  end  of  the  method  will  be  seen  each  grade  level  of  importance  of  each variable AHP. It describes the advantages in terms of where each model is used, so that the decision in the  form  of  a  score  variable  AHP  can  provide  valuable  information  for  anyone  who  will  take measurements  of  the  effectiveness  of  the  manuscript  copy.  Acquisition  synthesis  analysis  results obtained  based  on  the  priority  level  of  0.507  the  top  priority  is  DRM,  second  and  third  priorities respectively  0.327  and  0.166  for  the  EPIC  models  for  CRI,  this  is  becoming  a  final  decision  by  the AHP process.